State bureaucracy and the management of climate change adaptation in Bangladesh - Rahman, Md Saifur; Tosun, Jale (Review of policy research, 2018)
Bangladesh is widely regarded as a country that is heavily affected by the threats of climate change. In this study, we analyze the management of projects aiming to adapt to climate change in the period from 2009 to 2015. We are interested in two aspects: first, the overall bureaucratic setup of the adaptation regime, and second, the appointment of directors to the individual programs and what role foreign funding plays in making appointment decisions. With regard to the latter, it should be noted that project directors are an important arm of state bureaucracy in Bangladesh who guide the whole implementation and management of a development project, including its financial, regulatory, and informational dimensions. More specifically, we ask whether generalists or professionals are appointed as directors of the relevant projects. We argue and then show that the chances of appointing a professional as the director increase with the volume of foreign funding.